ปัจจัยเชิงเหตุและผลของพฤติกรรมการมีส่วนร่วมในโครงการความรับผิดชอบต่อสังคมของพนักงานบริการภาคพื้น บริษัท การบินไทย จำกัด (มหาชน) - เมืองโคตร, สรณัฐ; พันธุมนาวิน, ดุจเดือน (Journal of Behavioral Science for Development, 2018)
Corporate social responsibility (CSR) currently is one of the most important missions of large companies to develop and balance their profits back to generate sustainable development for society. The success of this mission is mainly depend on the participation of their organizational members. This study aimed at investigating the antecedents and consequences of participative behavior related to CSR of ground staffs in Thai Airways International, Results from path analysis reveal fit model (c2 = 58.201, df = 45, p-value = 0.0895, RMSEA = 0.026, CFI = 0.991, TLI = 0.981, SRMR = 0.048) and summarized as follow 1) Model supported the interactionism paradigm in terms of both psychological trait latent and situational factor latent directly and indirectly effect participative behavior related to CSR latent and outcome latent. 2) Psychological trait latent displayed the highest path coefficient to the outcome latent, followed by participative behavior related to CSR latent and situational latent which all together could explain the variance of the outcome latent for 34.2% 3) Psychological state latent displayed the highest path coefficient to the participative behavior latent, followed by situational latent and psychological trait latent which all together could explain the variance of the participative behavior related to CSR latent for 68.5% 4) In details, the findings suggested the importance of reducing materialism, enhancing supervisory social support, and heightened attitude towards CSR project to improve participative behavior relating to CSR in this organizational members.